MENINGITISES AMONG CHILDREN: PECULIARITIES OF THE PNEUMOCOCCAL MENINGITIS AND OPPORTUNITIES FOR THEIR VACCINE-BASED PREVENTION - M.G. Galitskaya; L.S. Namazova; A.G. Gaivoronskaya (Union of pediatricians of Russia, 2008)
This article reviews the urgent issue of the modern pediatrics - meningitis and its prevention. The authors explicitly highlighted the etiopathological aspects of the disease, defining both the clinical course of the disease and forecast. The extensive list of severe neurologic complications of the bacterial meningitises stipulated a necessity to look for the preventive events. Besides, growing antibiotic resistance and consequently effective meningitis therapy are not insignificant. The authors convincingly demonstrated that the basis for the prevention is vaccination among the most vulnerable groups of population - children younger than two years and elderly people. There is an opportunity for the «collective» immunity. Moreover, vaccination breaks the vicious circle of the growing resistance to antibiotics.Key words: meningitis, etiology, complications, forecast, prevention, children.